2016
DOI: 10.1371/journal.pbio.1002543
|View full text |Cite
|
Sign up to set email alerts
|

Sam68 Is Required for DNA Damage Responses via Regulating Poly(ADP-ribosyl)ation

Abstract: The rapid and robust synthesis of polymers of adenosine diphosphate (ADP)-ribose (PAR) chains, primarily catalyzed by poly(ADP-ribose) polymerase 1 (PARP1), is crucial for cellular responses to DNA damage. However, the precise mechanisms through which PARP1 is activated and PAR is robustly synthesized are not fully understood. Here, we identified Src-associated substrate during mitosis of 68 kDa (Sam68) as a novel signaling molecule in DNA damage responses (DDRs). In the absence of Sam68, DNA damage-triggered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 81 publications
1
55
0
Order By: Relevance
“…We recently revealed that Sam68 plays a crucial role in controlling DNA damage-induced PARP1 activation and PAR production; hence Sam68 deficiency dramatically dampens the PAR-dependent NF-κB signaling and DNA repair pathways initiated by DNA damage (Fu et al, 2016; Sun et al, 2016). As a key early signaling regulator that converges at the proxy of the DNA damage-triggered signaling cascade in the nucleus, Sam68 could provide a novel target for cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently revealed that Sam68 plays a crucial role in controlling DNA damage-induced PARP1 activation and PAR production; hence Sam68 deficiency dramatically dampens the PAR-dependent NF-κB signaling and DNA repair pathways initiated by DNA damage (Fu et al, 2016; Sun et al, 2016). As a key early signaling regulator that converges at the proxy of the DNA damage-triggered signaling cascade in the nucleus, Sam68 could provide a novel target for cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-body γ-irradiation (WBIR) in mice was performed as previously described (Sun et al, 2016). The γ-irradiated mice were sacrificed at indicated time points post WBIR for the indicated analyses, and the mortality and survival of mice were also monitored post γ-irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that Sam68 is an important early DNA damage signaling molecule that regulates DNA damage‐induced activation of poly(ADP‐ribose) polymerase 1 (PARP1) thus fulfilling an essential function in DNA repair and NF‐κB activation signaling pathways . As tumor cells generally acquire enhanced DNA repair activities to overcome the intrinsic DNA damage that frequently occurs during rapid proliferation, we sought to examine whether elevated levels of Sam68 in NMSC are essential for the cellular responses to DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…γ‐Irradiation of A431 cells and immortalized keratinocytes was performed using a 137 Cesium source (dose rate 8 Gy/min) as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation